The Effect of Electronic Word of Mouth Communication and Website Quality on Purchase Decisions through Trust as a Mediation Variable at Ruparupa.Com in Samarinda - Bagas Wicaksono Ihsan; Zainal Abidin; J. Kuleh (Budapest International Research and Critics University, 2022)
Along with the significant growth of internet users, online shopping has become an alternative for consumers to get the products they want. Various e-commerce competitively attract the attention of consumers such asruparupa.com. This study aims to analyze the effect of electronic word of mouth and website quality on purchase decisions either directly or through online trust mediation. This study took 65 consumers in Samarinda. Determination of the sample by purposive sampling technique. Data were collected through questionnaires and analyzed using partial least squares. The results of the analysis show that electronic word of mouth and website quality have a significant effect on online trust and purchase decisions. The study explains that online trust is able to play an intervening variable between electronic word of mouth and website quality on online trust and purchase decisions.